Night-time economy vitality index: Framework and evidence. Issue 3 (May 2022) - Lin, Vera Shanshan; Qin, Yuan; Ying, Tianyu; Shen, Shujie; Lyu, Guangming
This study aims to develop a multi-dimensional night-time economy vitality index (NTEVI) to measure the vitality of night-time economic (NTE) activities in Zhejiang Province, China, covering its 11 cities and 90 counties. Comprising 44 supply and demand indicators of the NTE, the index was composed of an overall index and six major sub-indices that measured the vitality of six typical NTE subsectors, including catering, shopping, recreation, accommodation, touring, and fitness. The NTEVI was calculated using a unique multi-source dataset based on hourly online transaction data from a leading Chinese online-to-offline service platform, monthly night-time electricity consumption data, and official statistics from 2019 to 2020. Robustness and sensitivity analyses were conducted to ensure high credibility of the index results. The findings of this study suggested that the NTEVI was highly and significantly correlated with night light indices, economic indicators, and tourism demand measures. By identifying regional and temporal differences across several service sectors over time at the county, city, and provincial levels, the NTEVI serves as a powerful numerical and visual tool: it offers key information to guide policy formulation, resource allocation, and policy evaluation. In the context of COVID-19, the index analyses also reflect the NTE recovery process in Zhejiang Province. Our findings indicate that it is important for the Chinese government, regional authorities, and enterprises to encourage the NTE as a main driver of economic revitalization.